2022
DOI: 10.1155/2022/9698138
|View full text |Cite
|
Sign up to set email alerts
|

First Presentation of Systemic Lupus Erythematosus in a 24-Year-Old Male following mRNA COVID-19 Vaccine

Abstract: The SARS-CoV-2 viral pandemic has had an immeasurable global impact, resulting in over 5 million deaths worldwide. Numerous vaccines were developed in an attempt to quell viral dissemination and reduce symptom severity among those infected. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of antinuclear autoantibodies (ANAs) with heterogenic clinical manifestations, secondary to immune complex deposition in a multitude of organ systems. There are scarcely reported cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
17
1
1
Order By: Relevance
“…The adverse events were negligible and there were no severe adverse events in both groups of SLE cases and healthy individuals after SARS-CoV-2 inactivated vaccine (31). This is in sharp contrast to other mentioned reports with increased side effects and flares with use of mRNA COVID-19 vaccines such as Pfizer/BioNTech (BNT162b2) (12)(13)(14)17,18,(20)(21)(22)(23)25,26), AZD1222 vaccine (15,16) and Moderna (19,24).…”
Section: Antibody Response Following Covid-19 Vaccination In Covid-19...contrasting
confidence: 60%
See 1 more Smart Citation
“…The adverse events were negligible and there were no severe adverse events in both groups of SLE cases and healthy individuals after SARS-CoV-2 inactivated vaccine (31). This is in sharp contrast to other mentioned reports with increased side effects and flares with use of mRNA COVID-19 vaccines such as Pfizer/BioNTech (BNT162b2) (12)(13)(14)17,18,(20)(21)(22)(23)25,26), AZD1222 vaccine (15,16) and Moderna (19,24).…”
Section: Antibody Response Following Covid-19 Vaccination In Covid-19...contrasting
confidence: 60%
“…A recent report also described a 24-year-old male who presented with positive ANA, and polyarthritis with joint pains with morning stiffness without a past medical history of autoimmune diseases, ten days following the first dose of the SARS-CoV-2 Pfizer-BioNTech mRNA vaccine (25).…”
Section: Review Of Published Cases Of Sle or Sle-like Syndromes Follo...mentioning
confidence: 99%
“…On the basis of the assumption that multisystem manifestations, such as SLE, that are temporally linked with pathogens are brought about by such pathogens through the induction of autoimmunity, the notion of vaccine-induced autoimmune response is suggested whenever such manifestations are temporally linked with vaccines. 24,25 But the light that the results presented here has thrown on the origin of the multisystem manifestations, which appeared to be autoimmune in the absence of such results, enables us to see that neither pathogens nor vaccines are the cause of such multisystem manifestations with which they are temporally linked.…”
Section: Discussionmentioning
confidence: 70%
“…Little is known about COVID-19 vaccination in patients with autoimmune skin diseases; however, cases of onset and exacerbation of cutaneous and systemic lupus erythematosus have been reported following the use of immunizers. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 This report describes a chronic cutaneous lupus erythematosus (CCLE) exacerbation thirty days after the second dose of ChAdOx1 nCoV-19 vaccine (Oxford/AstraZeneca).…”
mentioning
confidence: 99%
“… 3 The onset or exacerbation of lupus after vaccination is rare, with few cases in the literature. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 The international VACOLUP study indicated that COVID-19 vaccine was well tolerated in patients with systemic lupus erythematosus. Among the 696 participants assessed, only 3% reported a medically confirmed SLE flare after the immunization.…”
mentioning
confidence: 99%